Modeling of Tsunami Prone Areas in Kairatu Barat District, Seram Bangian Barat Regency - Rakuasa, Heinrich (PT. Riset Press International, 2024)
Modeling of tsunami-prone areas in Kairatu Barar Sub-district, Seram Bangian Barat Regency, is an important step in improving community safety and preparedness against tsunami threats. With this modeling, tsunami hazards can be better understood, more accurate early warning systems can be developed, and more effective risk reduction plans can be planned. In addition, the modeling also helps to improve people's understanding of tsunami hazards and the actions to be taken in emergency situations. The modeling results are instrumental in designing preventive measures, appropriate evacuation plans and improving disaster preparedness in the region, which can save lives and reduce damage from future tsunamis.